Kepemimpinan dan Kesetiaan Hamba Tuhan dalam Pelayanan di Era Postmodern Berdasarkan 2 Timotius 4:1-8 - Fa’ahakhododo Halawa; Malik Bambangan (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research aims to examine servant leadership and faithfulness in ministry in the postmodern era based on 2 Timothy 4:1-8. Using a qualitative method, it explores some of the scriptural texts and identifies the principles of leadership and faithfulness in ministry taught in Paul's letter to Timothy. Through this analysis, this study found that a servant of God's faithfulness in ministry must be based on the unchanging teaching of God's Word, even though the world around him continues to evolve in plurality and relativism. The main challenge for spiritual leaders is to maintain the truth of the Bible as the only authority in the face of various views that prioritize subjective and contextual truth. In the midst of postmodern trends that tend to relativize truth, spiritual leaders need to focus on the integrity of biblical teachings that are not influenced by culture or external pressures. In addition, this study emphasizes the importance of spiritual leaders' strategies in discerning sound teachings from heresies, emphasizing the need to understand the signs of heresies, such as rejection of biblical authority or interpretations that do not fit the historical and cultural context of the Bible. Spiritual leaders also need to remind congregants of their identity as citizens of the eternal Kingdom of God, by ensuring that they remain firmly grounded in the unshakeable truth of the Bible. The results of this study provide insights for spiritual leaders in facing the challenges of ministry in the postmodern era and provide guidelines for congregants to remain faithful to the teachings of the Bible amidst the development of a changing worldview as well as directing them to remain firm on the unshakeable foundation of biblical truth to maintain faithfulness to the true teachings of the Bible.